Hepsin regulates TGFβ signaling via fibronectin proteolysis. (13th September 2021) - Belitškin, Denis; Pant, Shishir M; Munne, Pauliina; Suleymanova, Ilida; Belitškina, Kati; Hongisto, Hanna‐Ala; Englund, Johanna; Raatikainen, Tiina; Klezovitch, Olga; Vasioukhin, Valeri; Li, Shuo; Wu, Qingyu; et al.
Abstract: Transforming growth factor‐beta (TGFβ) is a multifunctional cytokine with a well‐established role in mammary gland development and both oncogenic and tumor‐suppressive functions. The extracellular matrix (ECM) indirectly regulates TGFβ activity by acting as a storage compartment of latent‐TGFβ, but how TGFβ is released from the ECM via proteolytic mechanisms remains largely unknown. In this study, we demonstrate that hepsin, a type II transmembrane protease overexpressed in 70% of breast tumors, promotes canonical TGFβ signaling through the release of latent‐TGFβ from the ECM storage compartment. Mammary glands in hepsin CRISPR knockout mice showed reduced TGFβ signaling and increased epithelial branching, accompanied by increased levels of fibronectin and latent‐TGFβ1, while overexpression of hepsin in mammary tumors increased TGFβ signaling. Cell‐free and cell‐based experiments showed that hepsin is capable of direct proteolytic cleavage of fibronectin but not latent‐TGFβ and, importantly, that the ability of hepsin to activate TGFβ signaling is dependent on fibronectin. Altogether, this study demonstrates a role for hepsin as a regulator of the TGFβ pathway in the mammary gland via a novel mechanism involving proteolytic downmodulation of fibronectin. Synopsis: TGFβ is released from the ECM compartments of the mammary glands by hepsin mediated proteolytic cleavage of the ECM component fibronectin. Hepsin depletion in mice leads to impaired TGFβ signaling and increased mammary duct branching. Hepsin overexpression in an in vivo model of breast cancer activates TGFβ signaling. The extracellular matrix protein fibronectin is a target of proteolytic hepsin activity in vitro and in vivo. The regulation of TGFβ by hepsin requires proteolytic cleavage of fibronectin. Abstract : TGFβ is released from the ECM compartments of the mammary glands by hepsin mediated proteolytic cleavage of the ECM component fibronectin.